Prevalence And Comparative Analysis Of Clinical Pharmacist’s Treatment Related Interventions Across Four Icus At A Teaching Hospital - Massad, Eman MOh'd; Ashran, Walaa Jihad (Journal of Neonatal Surgery, 2025)
Background: Treatment-related problems (TRPs) are a significant concern in intensive care units (ICUs), where critically ill patients often require complex treatment regimens. Despite their high prevalence, TRPs can be reduced through effective clinical pharmacist interventions. This study aimed to identify and analyze TRPs across different ICU types at a tertiary hospital in Jordan and provide targeted recommendations to optimize pharmaceutical care. Methods: A retrospective descriptive analysis was conducted using data collected from ICU patients admitted between January and December 2024. The study focused on TRPs identified by clinical pharmacists in neonatal (NICU), medical (MICU), surgical (SICU), and pediatric (PICU) ICUs. Data on TRPs and pharmacist interventions were extracted from electronic medical records, categorized, and analyzed using descriptive statistics. Results: A total of 10,445 TRPs were identified across the four ICUs. The most frequent TRPs in the NICU were therapeutic drug monitoring (TDM) (34.98%) and dosage regimen issues (32.05%). In the SICU, TDM (37.21%) and medication reconciliation issues (25.58%) were predominant. The MICU exhibited the highest prevalence of dosage regimen problems (30.30%) and a notable need for additional diagnostic tests (12.52%). In the PICU, dosage regimen issues accounted for 38.86% of TRPs, followed by TDM (16.67%). Across all ICUs, the resolution of TRPs improved progressively throughout the study period, with 50% resolved by the fourth quarter. Conclusions: This study highlights the critical role of clinical pharmacists in managing TRPs and improving patient outcomes in ICUs. The findings emphasize the need for ICU-specific strategies, including enhanced TDM protocols, standardized dosing guidelines, and interdisciplinary collaboration, to address the unique challenges of each ICU type. These results provide a foundation for future quality improvement initiatives aimed at optimizing pharmaceutical care in critical care settings.